Incidence of diseases and pests in two groups of village sheep and goats in the forest zone of southwest Nigeria - Adeoye, S.A.O. (International Livestock Centre for Africa, 1985)
A study on the important diseases of village sheep and goats in the forest zone of southwest Nigeria, w., particularly emphasis on PPR, pneumonia, mange, helminthiasis, coccidiosis and babesiosis; w. data on liveweight gains of the animals interacting diseases w. nutritional stress on adequate feeding esp. supplementary feeding, prevents animals from succumbing to stress and disease.